Pengaruh Kualitas Pelayanan Jasa, Harga dan Fasilitas terhadap Kepuasan Pelanggan di PT Semenanjung Televisi Kabel - Trisna Mesra; Hanifatul Rahmi; M. Syahreza; Melliana, Melliana (Universitas Medan Area, 2024)
Customer satisfaction is the most crucial thing in the service business, so business owners need to pay attention to every aspect in increasing customer satisfaction. Customer satisfaction is the level of consumer feelings after comparing what they receive and their expectations. Satisfied consumers will be loyal longer, less sensitive to price and give good comments about the company. Based on these problems, it was done to find out whether the quality of service, price and facilities have a positive and significant effect on customer satisfaction at Semenanjung Cable Television. The data collection technique was through a questionnaire distributed to 147 respondents who were customers of Peninsula Cable Television. The method used in this study was Partial Least Square (PLS) with the help of SmartPLS software for data processing. The results showed that the service quality variable with a regression coefficient value of 0.125 did not have a significant effect on customer satisfaction. The Price variable with a regression coefficient value of 0.391 had a significant effect on customer satisfaction and the facility variable with a regression coefficient value of 0.382 had a significant effect on customer satisfaction. The service quality variable with a regression coefficient value of 0.4 has a significant effect on price and the facility variable with a regression coefficient value of 0.367 has a significant effect on price. From these results it can be concluded that the service quality variable has a positive but not significant effect on Customer Satisfaction at Semenanjung Cable Television. The price variable has a positive and significant effect on customer satisfaction at Peninsula Cable Television. The facility variable has a positive and significant effect on customer satisfaction at Semenanjung Cable Television.